2019
DOI: 10.1155/2019/9698086
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Drugs and Helicobacter pylori to Gastric Mucosa Changes in Patients with Systemic Lupus Erythematosus and Antiphospholipid Syndrome

Abstract: Background. The nature and rate of gastric mucosal (GM) damage in systemic lupus erythematosus (SLE) and antiphospholipid syndrome (APS) remain to be among the unsolved problems. Objective. To define the role of H. pylori and drugs in the development of GM damages in SLE and APS. Methods. A study was conducted on 85 patients with SLE and APS. All the patients underwent esophagogastroduodenoscopy with targeted biopsy of the mucosa of the gastric body and antrum. The presence of H. pylori in the gastric biopsy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 74 publications
0
5
0
1
Order By: Relevance
“…Reshetnyak et al [ 55 ] found significant differences in the detection rate of H. pylori with respect to the drugs used to treat SLE; the rate is higher with anticoagulant therapy (P = 0.038; OR = 2.96; 95% CI, 1.01–8.68) and low-dose acetylsalicylic acid (P = 0.031; OR = 3.58; 95% CI, 1.05–12.17) than for glucocorticoid and NSAID users. Nevertheless, Mendoza-Pinto et al [ 46 ] reported that immunosuppressive or glucocorticoid therapy did not increase the prevalence of H. pylori infection in patients with SLE.…”
Section: Helicobacter Pylori and Systemic Lupus Erythematosusmentioning
confidence: 99%
See 2 more Smart Citations
“…Reshetnyak et al [ 55 ] found significant differences in the detection rate of H. pylori with respect to the drugs used to treat SLE; the rate is higher with anticoagulant therapy (P = 0.038; OR = 2.96; 95% CI, 1.01–8.68) and low-dose acetylsalicylic acid (P = 0.031; OR = 3.58; 95% CI, 1.05–12.17) than for glucocorticoid and NSAID users. Nevertheless, Mendoza-Pinto et al [ 46 ] reported that immunosuppressive or glucocorticoid therapy did not increase the prevalence of H. pylori infection in patients with SLE.…”
Section: Helicobacter Pylori and Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Furthermore, there is no higher prevalence of gastroduodenal mucosal lesions or reflux disease in SLE patients with H. pylori infection than in the general population [ 46 , 55 ].…”
Section: Helicobacter Pylori and Systemic Lupus Erythematosusmentioning
confidence: 99%
See 1 more Smart Citation
“…Those who tested H. pylori positive in a polymerase chain reaction test had a lower frequency of gastric erosions. 35 Additional research is required to assess the relationship between H. pylori infection and the risk of gastroduodenal ulcers in lupus patients. Moreover, it remains to be clarified whether the use of NSAIDs has a positive or negative effect on H. pylori .…”
Section: Involvement By Locationmentioning
confidence: 99%
“…Reshetnyak и соавт. [47] пред ставлены данные о роли H. pylori и лекарственных препаратов в разви ти и п овреж д ен ий слизистой оболочки желудка (СОЖ) у пациентов с системной красной волчанкой (СКВ) и антифосфолипидны м си ндром ом (АФ С). У п ац иентов с СКВ и АФС при эндоскопическом исследовании вы являлись следующ ие изменения СОЖ: антральны й гастрит -у 82.4%, эрозии -у 24.7%, геморрагии -у 8.2%, пангастрит -у 8.2% пациентов.…”
Section: H Pylori и язвенная болезнь (яб)unclassified